2013
DOI: 10.1371/journal.pone.0064808
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Virus Infection in Eptesicus fuscus Bats Born in Captivity (Naïve Bats)

Abstract: The study of rabies virus infection in bats can be challenging due to quarantine requirements, husbandry concerns, genetic differences among animals, and lack of medical history. To date, all rabies virus (RABV) studies in bats have been performed in wild caught animals. Determining the RABV exposure history of a wild caught bat based on the presence or absence of viral neutralizing antibodies (VNA) may be misleading. Previous studies have demonstrated that the presence of VNA following natural or experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Based on our results, we hypothesize that rabies virus remains latent during hibernation and is recrudescent when bat are moved to ambient temperatures. Similar to previous studies, a homologous RABV was most pathogenic, regardless if bats were maintained at ambient temperatures or torpor [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based on our results, we hypothesize that rabies virus remains latent during hibernation and is recrudescent when bat are moved to ambient temperatures. Similar to previous studies, a homologous RABV was most pathogenic, regardless if bats were maintained at ambient temperatures or torpor [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 84%
“…To evaluate the presence of anti-rabies viral neutralizing antibodies (VNA), bats were bled from the uropatagial vein five weeks prior to inoculation to ensure seroconversion had not occurred. The rabies tissue culture serum neutralization test protocol was modified to reduce the amount of sample required to 25ul as previously described [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicate that primary exposure using a homologous RABV has virulence similar to that of exposure using a heterologous RABV. These results were unexpected; in a previous study with E. fuscus, infection with the homologous RABV was more likely to result in clinical illness than infection with a heterologous RABV (23). Streicker et al (2010) reported that although cross-species transmission events were uncommon, they occurred more frequently among closely related species (3).…”
Section: Discussionmentioning
confidence: 94%
“…Banerjee et al Virus Research 248 (2018) 5-12 viruses are discovered on a regular basis (Moratelli and Calisher, 2015;Schountz, 2014). Few viruses have been documented to cause disease in bats in addition to rabies and related lyssaviruses (Davis et al, 2012;Davis et al, 2013;McColl et al, 2002). Experimental inoculation of Jamaican fruit bats with high doses of Tacaribe virus caused significant morbidity and mortality similar to natural infection of artibeus bats (Downs et al, 1963).…”
Section: Using Cell Lines To Assess the Immune Response In Bats To VImentioning
confidence: 99%